2007
DOI: 10.1242/dev.02869
|View full text |Cite
|
Sign up to set email alerts
|

Conserved pattern of tangential neuronal migration during forebrain development

Abstract: Origin, timing and direction of neuronal migration during brain development determine the distinct organization of adult structures. Changes in these processes might have driven the evolution of the forebrain in vertebrates. GABAergic neurons originate from the ganglionic eminence in mammals and migrate tangentially to the cortex. We are interested in differences and similarities in tangential migration patterns across corresponding telencephalic territories in mammals and reptiles. Using morphological criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 74 publications
5
87
0
Order By: Relevance
“…Consistent with the previous finding that turtle MGE cells were able to migrate into the mouse neocortex in vitro (25), MGE cells from both chicken and turtle have the competency to migrate tangentially through the neocortical SVZ/IZ, and they have weak competency to enter neocortical layers 5 and 6 (Fig. S8B).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistent with the previous finding that turtle MGE cells were able to migrate into the mouse neocortex in vitro (25), MGE cells from both chicken and turtle have the competency to migrate tangentially through the neocortical SVZ/IZ, and they have weak competency to enter neocortical layers 5 and 6 (Fig. S8B).…”
Section: Discussionsupporting
confidence: 91%
“…This proposal is reasonable, but it may not be sufficient to fully explain the functional establishment of the neocortex, because it does not take into account the other essential component of the neocortex, interneurons, which invade from outside the pallium. Although the overall ratio of interneurons to the total number of neurons in the dorsal pallium varies among amniotes (20)(21)(22)(23), the tangential migration of interneurons from the MGE to the dorsal pallium is highly conserved across gnathostomes, including amniotes (24)(25)(26)(27)(28), and ∼75% of interneurons in the chicken pallium originate from the MGE (24). Interestingly, the mechanism of the tangential migration seems to be conserved across amniotes (25), suggesting that the common mechanism of tangential migration from the MGE to the dorsal pallium was already established in the ancestor of amniotes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on analogy of connectivity, Karten (1997) suggested that the redistribution by tangential migration of cells generated by the DVR (dorsal ventricular ridge) domain, a derivative of the VP/LP in birds and reptiles, contributed to form the neocortex. However, until recently, tangential migration of glutamatergic cells from the VP/PSB toward the dorsal pallium was not demonstrated in mammals and was further excluded to occur in sauropsids (Métin et al, 2007).…”
Section: Acquisition Of Dbx1-derived Transient Neurons At the Psb Andmentioning
confidence: 99%
“…With the possible exception of human and nonhuman primates (Letinic et al, 2002), cortical GABAergic interneurons seem to derive almost exclusively from the subpallium in all vertebrates studied so far (Anderson et al, 1997(Anderson et al, , 2002Cobos et al, 2001a;González et al, 2002;Stühmer et al, 2002;Brox et al, 2003;Tuorto et al, 2003;Mueller et al, 2006;Fogarty et al, 2007;Métin et al, 2007;Xu et al, 2008) and reach the cortex through a long tangential migration (Corbin et al, 2001;Rubenstein, 2001, 2003;Métin et al, 2006). In particular, the medial ganglionic eminence (MGE) and the caudal aspect of the lateral ganglionic eminence (cLGE) [also known as the dorsal aspect of the caudal ganglionic eminence (dCGE)] have been suggested to generate most cortical GABAergic interneurons (Xu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%